Differences in calcification and osteogenic potential of herniated discs according to the severity of degeneration based on Pfirrmann grade: a cross-sectional study. Issue 1 (December 2016) - Shao, Jia; Yu, Miao; Jiang, Liang; Wei, Feng; Wu, Fengliang; Liu, Zhongjun; Liu, Xiaoguang
Abstract Background Herniated discs may exhibit calcification, and calcified discs may complicate surgical treatment. However, the osteogenic potential and expression of osteogenic markers in degenerative discs of different degenerative grades are still unclear. Our purposes are to study the differences in calcification rate and osteogenic potential of herniated discs according to different degenerative grades. Methods Fifty-eight lumbar intervertebral discs were removed from 41 patients. After grading according to the Pfirrmann scale, calcification was analyzed by micro computed tomography (μ-CT), and expression of osteogenic markers was analyzed by immunohistochemistry and real-time quantitative polymerase chain reaction (qPCR). Data from μ-CT scans were compared with the Kruskal–Wallis test. The Mann–Whitney test was applied to compare data between any two groups. Differences in osteogenic mRNA expression in different regions of the removed discs (posterior vs. anterior) were analyzed by pairedt tests. Differences in the posterior portion of removed discs of different Pfirrmann grades were analyzed by one-way analysis of variance (ANOVA), and comparisons of data between discs of any two grades were completed with least significant difference (LSD) tests. Results Significant differences in calcification according to μ-CT scanning were observed between discs of different degenerative grades. Nearly half of the discs of Pfirrmann grade V showed the highest degree of calcification compared to Pfirrman grade II discs. Bone morphogenetic protein (BMP)-2, Osterix, and Osteocalcin were detected histologically in discs of Pfirrmann grades III–V. Alkaline phosphatase (ALP) expression was observed in discs showing evidence of calcification. The qPCR analysis showed that BMP-2, Osterix, and Osteocalcin were expressed in most degenerated discs. We also observed greater expression of these osteogenic markers in the posterior portion of removed discs than in the anterior portion. Conclusions The osteogenic potential of degenerated intervertebral discs appears to increase with the severity of degeneration and to be greater in the tissue near the spinal canal than in tissue in the inner portion of the disc.